INNOVATIVE HOSE WASHER NOZZLE SEBAGAI SARANA PEMELIHARAAN SELANG PEMADAM PKP - Muh Tri Kurniawan; Nawang Kalbuana; Surya Tri Saputra (MANAJEMEN, 2025)
This study aims to design an auxiliary tool called the Innovative Hose Washer Nozzle as a solution for maintaining fire hoses within the Aircraft Rescue and Firefighting (ARFF) Study Program at the Indonesian Aviation Polytechnic Curug. The main problem addressed is the manual cleaning of fire hoses, which requires considerable time and effort and may reduce the hose’s lifespan. Using a Research and Development (R&D) method based on a simplified Borg & Gall model comprising six stages, the tool was designed, validated by experts and users, and tested in an operational setting. The test results show that the Innovative Hose Washer Nozzle significantly improves the effectiveness and efficiency of hose cleaning, achieving an 80% cleanliness level, reducing cleaning time to only 5 minutes, and reduced cleaning time to 5 minutes with fewer personnel, achieving 80% cleanliness and 77.5% feasibility score. This innovation contributes to the improvement of safety equipment maintenance, operational readiness, and work efficiency for cadets during both training and emergency operations.